(3CSQGQ GdYQHjIs - (3YHO GdQMef Hf eMeO Hf YHjO Gddg GdCfUGQj , GHf GdCfHGQj, ceGd GdOjf CHh GdHQcGJ,J (B577 (3g` s ((3HZOGO s)
(3ChdgG (B:s
(3GdMeO ddg cGTa GdZWGA heGfM GdYWGA Pi GdGHJOG hGdEYGOI s
(3BNQgG (B:s
(3Je GdcJGH hGdMeO ddg QH GdYGdejfq s
(3Vef eLehY , JQJjHgG (B: 1s
(3HChd GdeNWhW agQSJs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B104s
Keywords: (3GdfMhs